Synthesis, Sintering, and Electrical Properties of BaCe0.9−xZrxY0.1O3−δ. (28th September 2008) - Ricote, S.; Caboche, G.; Estournes, C.; Bonanos, N.
Abstract : BaCe 0.9 − x Zr x Y 0.1 O 3 − δ powders were synthesized by a solid-state reaction. Different contents of cerium and zirconium were studied. Pellets were sintered using either conventional sintering in air at1700 ∘ C or the Spark Plasma Sintering (SPS) technique. The density of the samples sintered by SPS is much higher than by conventional sintering. Higher values of ionic conductivity were obtained for the SPS sample.